Role of Marine Metabolites in Shrimp Growth, Production and Disease Prevention - Nishanth Lipton, Anuj; Selvin, Joseph; Kiran, Seghal; Premnath Lipton, Aaron (Facultad de Ciencias Biologicas, 2017)
This review consolidates the recent information about the global aquaculture production status of fish andshellfish. Research reports on common and emerging microbial diseases of cultivable species of shrimp arenarrated together with resultant reductions in productivity. The harmful effects antibiotics usage in shrimpaquaculture and consequent effects on the species as well as ecosystem are highlighted. The in vitro and invivo tests of extracts containing metabolites isolated from marine macroalgae, sea grasses and invertebrates inrestraining the proliferation of disease causing microbes are presented. The metabolite bearing marine speciesand methods of extraction of marine metabolites are concisely indicated. Studies on unique bacteriaassociated with the metabolite - bearing marine organisms, their identity and their significance in metaboliteproduction are essential for future research and developmental activities in aquaculture and pharmaceuticalapplications. The administration of marine metabolites in the post larval and juvenile shrimps as feed additivefor controlling the common microbial diseases such as vibriosis together with essential administrationprotocols are reported. Many of the tested marine metabolites are of immense use as they increased thesurvival of farm reared shrimps and their growth rates. The resultant specific growth rate attained togetherwith survival contributed to the significant increase in production. Perusal of literature indicated that marinesecondary metabolites isolated from marine macro algae and sponges exhibited immune enhancing activity inshrimps in a non specific manner when administered as a feed ingredient.